Abstracts Accepted for Publication 2019
DOI: 10.1136/annrheumdis-2019-eular.1978
|View full text |Cite
|
Sign up to set email alerts
|

Ab0790 evaluating the Effectiveness of Intra-Articular Knee Injection Using Allogenic Platelet Derived Lyophilized Growth Factors in Egyptian Patients With Symptomatic Primary Knee Osteoarthritis

Abstract: BackgroundUsing intra-articular injections of autologous platelet-rich plasma (PRP) has showen promising results in treatment of knee osteoarthritis (KOA). Its regenerative properties depends on the amount of growth factors (GF) released after platelets activation. Using large-volume of blood for obtaining allogenic PRP can provide higher concentrations of platelet and GF. However once prepared, PRP is stable for only 8-hours. Freeze drying (lyophilization) can be used to stabilize the biological materials for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…However, L-GFs have not been well studied. 22 Elgohary et al 11 have investigated the effectiveness of intra-articular injection of allogeneic L-GFs in Egyptian patients with symptomatic knee OA. They concluded that allogeneic L-GFs showed encouraging results and were well tolerated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, L-GFs have not been well studied. 22 Elgohary et al 11 have investigated the effectiveness of intra-articular injection of allogeneic L-GFs in Egyptian patients with symptomatic knee OA. They concluded that allogeneic L-GFs showed encouraging results and were well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…L-GFs are suitable for intralesional injection as it is a water-soluble product with no gel formation. 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogeneic platelet-derived growth factors injection was reported for treatment of plantar fasciitis and knee osteoarthritis [ 9 , 10 ]. They include platelet-derived growth factor (PDGF), transforming growth factor beta (TGFS-β), epidermal growth factor (EGF), vascular endothelial growth factor (VEGF) and insulin-like growth factor [ 1 , 2 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has growth factors concentration equivalent to an autologous PRP preparation obtained from 20 mL of whole blood with a platelet count of 106/μL, but with a much longer shelf life (12–18 months versus only 8 hours). It is suitable for local intralesional injection being a water-soluble product with no gel formation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%